Factors Influencing Decisions to Purchase Counterfeit Fashion Products: Brand Image, Price and Lifestyle (Literature Review Customer Behavior) - Wawan Novianto; Zebua, Ali Marzuki; Mursal (Dinasti Research, 2021)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence purchasing decisions for counterfeit fashion products, namely: brand image, price and lifestyle, a literature study of consumer behavior. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article are: 1) brand image influences purchasing decisions for counterfeit fashion products; 2) price has an effect on purchasing decisions for counterfeit fashion products; and 3) lifestyle influences purchasing decisions for counterfeit fashion products.